Two new species in the genus Geritola Libert, 1999 (Lepidoptera: Lycaenidae, Epitolini) - Sáfián, Szabolcs; Collins, Steve C.; Libert, Michel; Libert, Michel (Zootaxa, 2015)
Two Geritola (Lepidoptera: Lycaenidae) species, closely related to the Central African G. nitidica, have been recognised as new to science. G. wardi sp. n. was captured in small series in Mabira, an eastern outlier forest in Uganda, while G. pacifica sp. n. was discovered in Liberia, in classic Upper-Guinean hyper-wet rainforests. Both of them are described in comparison to their allopatric relative G. nitidica, including male genitalia.